Kinetics of intramolecular chemical exchange by initial growth rates of spin saturation transfer difference experiments (SSTD NMR)1. Issue 50 (25th June 2015) - Quirós, M. Teresa; Angulo, Jesús; Muñoz, María Paz
<x xml:space="preserve">Abstract</x> Initial growth rates SSTD NMR method is a new powerful tool to obtain the kinetic parameters of intramolecular chemical exchange.